A watermarking technique to improve the security level in face recognition systems: An experiment with Principal Component Analysis (PCA) for face recognition and Discrete Cosine Transform (DCT) for watermarking - Isa, Mohd Rizal Mohd Mohd; Yusoff, Zaharin; Aljareh, Salem; Jacey-Lynn, Minoi (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents a proposal for a suitable and viable combination of a face recognition system and a watermarking system, with a watermarking technique that will ensure the authenticity of the data being transmitted in the face recognition system, which will then enhance its level of security. The proposed combination is a PCA-DCT system. © 2016 IEEE.